Adolescents' perspectives on soft drinks after the introduction of the UK Soft Drinks Industry Levy: A focus group study using reflexive thematic analysis. (1st December 2022) - Jones, Catrin P.; Armstrong-Moore, Roxanne; Penney, Tarra L.; Cummins, Steven; Armitage, Sofie; Adams, Jean; White, Martin
Abstract: Background: The UK Soft Drinks Industry Levy (SDIL), announced in March 2016 and implemented in April 2018, is a fiscal policy to incentivise reformulation of eligible soft drinks. We aimed to explore perceptions of sugar, sugary drinks and the SDIL among adolescents in the UK post-implementation. Methods: 23 adolescents aged 11–14 years participated in four focus groups in 2018–2019. A semi-structured topic guide elicited relevant perspectives and included a group task to rank a selection of UK soft drinks based on their sugar content. Braun and Clarke's reflexive thematic analysis was used to undertake inductive analysis. Results: Four main themes were present: 1) Sweetened drinks are bad for you, but some are worse than others; 2) Awareness of the SDIL and ambivalence towards it 3) The influence of drinks marketing: value, pricing, and branding; 4) Openness to population-level interventions. Young people had knowledge of the health implications of excess sugar consumption, which did not always translate to their own consumption. Ambivalence and a mixed awareness surrounding the SDIL was also present. Marketing and parental and school restriction influenced their consumption patterns, as did taste, enjoyment and consuming drinks for functional purposes (e.g., to give them energy). Openness to future population-level interventions to limit consumption was also present. Conclusions: Our findings suggest that adolescents are accepting of interventions that require little effort from young people in order to reduce their sugar consumption. Further education-based interventions are likely to be unhelpful, in contexts where adolescents understand the negative consequences of excess sugar and SSB consumption.